Investigação da deterioração fúngica de empanados congelados de frango: origem da contaminação e resistência térmica dos deteriorantes - Wigmann, Évelin Francine (2015)
The food industry has changed in recent decades the focus of the production, since the eating habits of consumers have been directed to practical, fast and tasty foods. So, breaded frozen chicken were created, one of the biggest hits of the fast food industry. This class of pre-made and frozen products allows for long-term storage and can select species of microorganisms capable of growing in low temperatures, especially filamentous psychrophilic fungi. Despite annual losses are estimated at 1 to 1.5 % by fungal spoilage of frozen chicken nuggets, rare are the available scientific data. The objective of this study was to conduct a general mycological investigation of a processing industry of frozen chicken nuggets, analyzing the raw materials, the products in different processing steps and the ambient air of each unit of operation. It was also analyzed the effect of heating treatments applied in the manufacture of the nugget on inactivation of Penicillium commune (NGT 16/12), Penicillium polonicum (NGT NGT 23/12 and 33/12), Penicillium glabrum (NGT 29/12 and NGT 35/12), Penicillium solitum (NGT 30/12) and Penicillium crustosum (NGT 51/12), main species related to deterioration of these products. The flour exhibited counts between 101 and 104 CFU/mL, predominating species P. polonicum, Aspergillus flavus, Aspergillus candidus, Penicillium citrinum and Eurotium amstelodami. The following processed samples showed a steady reduction in scores for 101 CFU/g, with a predominance of P. polonicum. In the other hand, regarding the samples of final product analyzed, 10% were contaminated by P. glabrum, with was also the most predominant species of spoilers in the air environment. The results show that the P. polonicum (NGT 23/12), P. commune (NGT 16/12), P. solitum (NGT 30/12) and P crustosum (NGT 51/12) were able to survive to the heat treatments applied (fried by immersion in oil at 195-200 °C for 6 seconds), and baking in oven at 120-130 °C until the internal temperature reached 70 °C when inoculated in the frozen chicken nuggets. Additionally, it was observed that P. polonicum (NGT 23/12), was the most heat resistant species, recovering counts of 104 CFU/g after frying for 6 minutes and 30 seconds of cooking, having 2,02 log CFU/g reduced at 72 °C and 3,29 log CFU/g reduced at 78 °C in the internal of the product during the baking. According to the results it was observed that both the flour used to manufacture breaded as the air industry environment pose a hazard, then strategies must be taken to reduce the presence of fungal spores in this points, possible sources of these fungal contamination.